Pertamina Retail's Legal Responsibilities in Self Service Services - Wirayuda, Kevin Agung; Mardijono, H.R Adianto (Activa Yuris: Jurnal Hukum, 2025)
Self-service technologies (SST) are technological intermediaries that enable customers to produce their own services. Recently, self-service services at gas stations have become popular among consumers. This service allows customers to refuel their vehicles without the help of gas station attendants. This gives customers the flexibility and convenience of refueling according to their needs. This self-service technology is proven to provide convenience and efficiency for the public in refueling. The most important thing in refueling is consumer safety and risk. Apart from that, self-service technology is also available. There are no special government regulations for PT. Pertamina.